Toxicity and Toxicokinetic Study of Subcutaneously Administered RPh201 in Minipigs. (August 2018) - Ramot, Yuval; Hazan, Zadik; Lucassen, Andre; Adamsky, Konstantin; Ross, Vanessa; Young, Nigel; Saunders, Matt; Ehall, Helmut; Nyska, Abraham
Mastic gum extracts are widely used as herbal remedies and are being tested for several clinical indications. Nevertheless, information on their safety is limited. RPh201 is an extract of the mastic gum, formulated and stabilized in a proprietary method, which is being developed as a novel drug candidate for neurological indications. The aim of this study was to assess the systemic toxic potential of RPh201, administered twice weekly by subcutaneous injections to minipigs, after 39 weeks of administration followed by a recovery period of 6 weeks. No clinical or dose-related signs were observed, but treatment-related findings were seen at the injection sites of the high-dose animals, composed of abscesses, chronic inflammation, and subcutaneous fibrosis. Abscesses >30 mm in size, graded as marked severity, were confined to the high-dose group and were considered as adverse. Minimal-slight subcutaneous and lymph nodes abscesses seen in control, low, and intermediate doses, related to the vehicle (cottonseed oil), were not considered as adverse. Additionally, minimal-to-slight cystic spaces or vacuolation related to the vehicle were observed in the skin, lymph nodes, kidney, and lungs. These findings were considered not to be adverse. The no-observed-adverse-effect level was considered to be 12.5 mg/kg/occasion.